PENJATUHAN PIDANA PENJARA DIBAWAH ANCAMAN MINIMUM KHUSUS TERHADAP PELAKU TINDAK PIDANA NARKOTIKA (Studi Putusan Nomor: 220/Pid.Sus/2017/PN Pwt) - Yoga Pratama; Sanyoto Sanyoto; Dessi Perdani Yuris (Soedirman Law Review, 2020)
One of the criminal code products outside the codification that adheres to a special jurisdiction is constitution number 22 of 1997 concerning narcotics as amanded by contitution number 35 of 2009 concerning narcotics. The provision of special minimum criminal threats the judge may not impose imprisonment under the special minimum threat. In this criminal problem which is decided by the Purwokerto District Court on decision number: 220/Pid.Sus/2017/PN Pwt, the panel of judges has convicted the defendant under the provisions of the special minimum threat that has been determined by law. The aim of this research is determine the criminal prosecution below the special minimum in Decision Number: 220 / Pid.Sus / 2017 / PN Pwt in terms of proof theory, idling theory, the purpose of Law Number 35 Year 2009, the principle of legality (Nulla Poena SinaLege) , the purpose of legislation and to find out legal considerations in the Decision Number: 220 / Pid.Sus / 2017 / PN Pwt. In this legal research using the Law approach, and the case approach, with prescriptive research specifications. In this study the legal materials used consisted of primary legal materials and secondary legal materials. The analyzed legal material is presented in the form of a systematic, logical and rational description. Of the research on the results of the study, it can be concluded that the imprisonment below the specific minimum in Decision Number: 220 / Pid.Sus / 2017 / PN Pwt is contrary to the objectives of Law Number 35 Year 2009, the principle of legality (Nulla Poena Sina Lege), the purpose of legislation, and the panel of judges in imposing imprisonment below the specific minimum does not provide enough consideration so that legalconsiderations in Decision Number: 220 / Pid.Sus / 2017 / PN Pwt can be categorized as decisions that lack sufficient legal considerations (Onvoldoende Gemotiveerd ) Keywords : Imprisonment below the specific minimum, proof theory, and theobjectives of Law Number 35 Year 2009